Biomechanics of an Articulated Screw in Acute Scapholunate Ligament Disruption - Hiro, Matthew E.; Schiffman, Corey J.; Muriuki, Muturi G.; Havey, Robert M.; Voronov, Leonard I.; Bindra, Randy R. (Journal of Wrist Surgery, 2018)
Background An injury to the scapholunate interosseous ligament (SLIL) leads to instability in the scapholunate joint. Temporary fixation is used to protect the ligament during reconstruction or healing of the repair. Rigid screw fixation—by blocking relative physiological motion between the scaphoid and lunate—can lead to screw loosening, pullout, and fracture.Purpose This study aims to evaluate changes in scaphoid and lunate kinematics following SLIL injury and the effectiveness of an articulating screw at restoring preinjury motion.Materials and Methods The kinematics of the scaphoid and lunate were measured in 10 cadaver wrists through three motions driven by a motion simulator. The specimens were tested intact, immediately following SLIL injury, after subsequent cycling, and after fixation with a screw.Results Significant changes in scaphoid and lunate motion occurred following SLIL injury. Postinjury cycling increased motion changes in flexion-extension and radial-ulnar deviation. The motion was not significantly different from the intact scapholunate joint after placement of the articulating screw.Conclusion In agreement with other studies, sectioning of the SLIL led to significant kinematic changes of the scaphoid and lunate in all motions tested. Compared with intact scapholunate joint, no significant difference in kinematics was found after placement of the screw indicating a correction of some of the changes produced by SLIL transection. These findings suggest that the articulating screw may be effective for protecting a SLIL repair while allowing the physiological rotation to occur between the scaphoid and lunate.Clinical Relevance A less rigid construct, such as the articulating screw, may allow earlier wrist rehabilitation with less screw pullout or failure.
Keywords: scapholunate interosseous ligament injury; scaphoid and lunate kinematics; screw fixation; flexion-extension; radial-ulnar deviation; dart-thrower's motion; biomechanics